High-temperature-resistant high-strength underwater recycled airbag material for floating device of underwater equipment

By using underwater recycling airbag material composed of high-strength fiber base cloth and silicone rubber coating, the problem of the existing materials deteriorating strength in high-temperature environments is solved, and the dual performance of high strength and high temperature resistance is achieved.

CN119663643APending Publication Date: 2025-03-21INNER MONGOLIA INST OF SYNTHETIC CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411930694.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing underwater recycling airbag materials cannot meet the requirements of high strength and high temperature resistance at the same time, and there is a risk of damage in a high-temperature environment.

Method used

The material consists of high-strength fiber base cloth and silicone rubber coating. The high-strength fiber base cloth is composed of aramid fiber or polyimide fiber filaments. The base cloth is coated with silicone rubber coating respectively. The silicone rubber coating is composed of silicone elastomer and inorganic filler, providing wear resistance, puncture resistance, thermal protection and gas barrier functions.

Benefits of technology

The material's appearance did not change significantly after 120 seconds of high-temperature gas blowing at 350℃, and its strength decreased by only 5%-8%, showing excellent heat resistance and high strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663643A_ABST
    Figure CN119663643A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant and high-strength underwater recycled air bag material for a floating device of underwater equipment. The underwater recycled air bag material is composed of high-strength fiber base cloth and silicone rubber coatings on the upper portion and the lower portion of the base cloth. The base cloth is made of aramid fibers or polyimide fibers, the surface density is 200-400 g / m < 2 >, the coating weight of the lower-layer silicon rubber is 400-700 g / m < 2 >, the coating weight of the upper-layer silicon rubber is 200-420 g / m < 2 >, and the lower layer and the upper layer correspond to the inner side and the outer side of the air bag after the air bag is formed respectively; the silicone rubber coating is formed by a mixture of an organic silicone elastomer and an inorganic filler. The high-temperature-resistant high-strength underwater recycled airbag material has excellent strength and high-temperature resistance, and the strength is reduced by 5-7% after the material is blown by hot air at 350 DEG C for 120 s.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an air bag material, in particular to a high-temperature resistant and high-strength underwater recovery air bag material used for an underwater equipment flotation device. Background Art

[0002] The underwater recovery airbag is an important part of the underwater equipment floating recovery device. By inflating the underwater recovery airbag, the underwater equipment is provided with the positive buoyancy required for surface recovery. At present, the inflation method adopted by the floating device is generally that the equipment carries a high-pressure gas cylinder as the gas source. However, the high-pressure gas cylinder will produce a large redundant load. With the increasing requirements for the recovery device, more and more recovery devices use gas generators as the gas source to inflate the underwater recovery airbag.

[0003] The high-temperature gas produced by the gas generator will cause thermal shock to the underwater recovery airbag material. Traditional airbags made of polyurethane or rubber cannot withstand high temperatures and are at risk of damage. As the recovery depth increases, the inflation pressure of the underwater recovery airbag will also increase. This requires the underwater recovery airbag material to have both high strength and high temperature resistance. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a high-temperature resistant and high-strength underwater recovery airbag material for underwater equipment flotation devices, so as to solve the problem that the existing underwater recovery airbag materials used for underwater equipment flotation devices cannot meet the requirements of high strength and high temperature resistance at the same time.

[0005] In order to solve the existing technical problems, the technical solution adopted by the present invention is: a high-temperature resistant and high-strength underwater recovery airbag material for underwater equipment floating device, which is composed of a high-strength fiber base cloth and an upper silicone rubber coating and a lower silicone rubber coating. The high-strength fiber base cloth is composed of aramid fiber filaments or polyimide fiber filaments; the upper silicone rubber coating and the lower silicone rubber coating are respectively coated on the inner and outer sides of the high-strength fiber base cloth, corresponding to the inner and outer sides of the airbag after the airbag is formed;

[0006] The components and proportions of the upper silicone rubber coating are:

[0007] Silicone elastomer………………100 parts

[0008] Functional filler…………10~20 parts

[0009] Vulcanizing agent…………1~10 parts

[0010] The components and proportions of the lower silicone rubber coating are:

[0011] Silicone elastomer 100 parts

[0012] Inorganic filler…………20~30 parts

[0013] Vulcanizing agent…………1~10 parts

[0014] Wherein, the organic silicon elastomer is one or a mixture of vinyl silicone rubber, vinyl phenyl silicone rubber, hydroxyl-terminated silicone rubber and hydroxyl-terminated phenyl silicone rubber.

[0015] Furthermore, the high-strength fiber base cloth of the present invention preferably adopts a woven structure.

[0016] Furthermore, the weaving structure of the high-strength fiber-based cloth of the present invention is preferably a plain weave, a twill weave or a square basket structure.

[0017] Furthermore, the fiber filament denier of the present invention is preferably 300-2000D.

[0018] Furthermore, the surface density of the high-strength fiber-based fabric of the present invention is preferably 200-400 g / ㎡.

[0019] Furthermore, the surface density of the lower silicone rubber coating of the present invention is preferably 400-700 g / ㎡.

[0020] Furthermore, the surface density of the upper silicone rubber coating of the present invention is preferably 200-420 g / ㎡.

[0021] Furthermore, the functional filler of the present invention is preferably one or a mixture of iron oxide, silicon dioxide, flaky graphite, talcum powder, molybdenum disulfide or tetrafluoroethylene powder.

[0022] Furthermore, the inorganic filler of the present invention is preferably one or a mixture of iron oxide, silicon dioxide, carbon black, flaky graphite, lanthanum oxide, boron oxide, calcium silicate, mica powder or kaolin.

[0023] Furthermore, the viscosity of the upper silicone rubber coating and the lower silicone rubber coating of the present invention is preferably 4000-20000 CPS.

[0024] The silicone rubber coating of the present invention is composed of organic silicone elastomer and inorganic filler. The main functions of the upper silicone rubber coating are wear resistance and puncture resistance; the functions of the lower silicone rubber coating are heat protection and gas barrier.

[0025] The organosilicon elastomer and the corresponding functional filler or inorganic filler are mixed evenly using a three-roll grinder, and the corresponding vulcanizing agent is added and mixed evenly.

[0026] The coating amount of the lower silicone rubber coating on the lower layer of the base fabric is 400-700g / ㎡, which plays the main functions of heat protection and gas barrier, and the coating amount of the upper silicone rubber coating on the upper layer of the base fabric is 200-420g / ㎡, which plays the functions of wear resistance and puncture resistance. The lower and upper silicone rubber coatings of the base fabric correspond to the inner and outer sides of the airbag after the airbag is formed.

[0027] The high-temperature resistant and high-strength underwater recovery airbag material of the present invention has excellent temperature resistance. After being blown by high-temperature gas at 350° C. for 120 seconds, the appearance does not change significantly, and the strength decreases by 5%-8%.

[0028] Beneficial Effects

[0029] The present invention is composed of a high-strength fiber base cloth and silicone rubber coatings above and below the base cloth, wherein the high-strength fiber base cloth is composed of aramid fiber or polyimide fiber filaments, the base cloth can be realized by weaving, preferably, the weaving structure can be a plain, twill or square flat structure, and the silicone rubber coating is composed of an organic silicone elastomer and an inorganic filler. The main functions of the upper silicone rubber coating are wear resistance and puncture resistance; the function of the lower silicone rubber coating is thermal protection and air barrier. The high-temperature resistant and high-strength underwater recovery airbag material of the present invention has the characteristics of high tensile strength, good heat resistance and puncture resistance, and a soft body that can be folded multiple times. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The schematic diagram of the structure of the high-temperature resistant and high-strength underwater recovery airbag material of the present invention includes: a high-temperature resistant and high-strength underwater recovery airbag material 1, a base fabric 3, an upper silicone rubber coating 2, and a lower silicone rubber coating 4;

[0031] Figure 2 A schematic diagram of the folding of the high temperature resistant and high strength underwater recovery airbag material of the present invention;

[0032] Figure 3 This is a diagram of the apparent state of Example 2 of the high-temperature resistant and high-strength underwater recovery airbag material of the present invention after the heat resistance test. DETAILED DESCRIPTION

[0033] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0034] like Figure 1 As shown, the high temperature resistant and high strength underwater recovery airbag material 1 of the present invention comprises a base fabric 3, an upper silicone rubber coating 2 and a lower silicone rubber coating 4.

[0035] The base fabric 1 may be made of para-aramid fiber or polyimide fiber filament plain weave fabric, and the denier of the filament may be between 300-2000D, such as 400D, 600D, 800D, 1000D, 1200D, 1500D, 1800D, etc.

[0036] The upper silicone rubber coating 2 silicone rubber elastomer of the high temperature resistant and high strength underwater recovery airbag material 1 of the present invention can be phenyl silicone rubber, and the inorganic filler can be iron oxide. The coating viscosity is between 6000-8000 CPS, and the coating amount is 200-420 g / ㎡.

[0037] The lower silicone rubber coating 4 silicone rubber elastomer of the high temperature resistant and high strength underwater recovery airbag material 1 of the present invention can be phenyl silicone rubber, and the inorganic filler can be iron oxide or silicon dioxide. The coating viscosity is between 6000-8000 CPS, and the coating amount is 400-700g / ㎡.

[0038] Experimental methods:

[0039] Heat resistance test: Cut the sample into a 200×200mm square, fix the edge of the sample on the frame, and fix the relative position of the hot air gun nozzle to the sample at a distance of 1cm. Heat the sample with a hot air gun, and the outlet temperature of the hot air gun is 350℃. After blowing for 120s, take the sample off and observe the appearance. Cut the blown part of the material into tensile specimens for strength testing.

[0040] Strength test: Cut the sample into 200×25mm strips and use a tensile machine to test the tensile strength of the material.

[0041] Embodiment 1:

[0042] Polyimide plain fabric with a denier of 400D was used. The silicone rubber coating was composed of phenyl silicone rubber and iron oxide, with a viscosity of 6000CPS, an upper coating amount of 200g / ㎡, and a lower coating amount of 500g / ㎡. The tensile strength of the material before and after the heat resistance test was tested, and the results are shown in Table 1.

[0043] Components and proportions of the upper silicone rubber coating:

[0044] Vinyl phenyl silicone rubber (viscosity 6000CPS)……………100 parts

[0045] White carbon black 5 parts

[0046] Flake graphite………………5 parts

[0047] Talc powder………………5 parts

[0048] Iron oxide………………1 part

[0049] Hydrogenated silicone oil (platinum catalyst) 1 to 10 parts

[0050] Components and proportions of the lower silicone rubber coating:

[0051] Vinyl phenyl silicone rubber (viscosity 6000CPS)……………100 parts

[0052] White carbon black 5 parts

[0053] Boron oxide 5 parts

[0054] Calcium silicate 5 parts

[0055] Iron oxide………………1 part

[0056] Mica powder………………5 parts

[0057] Hydrogenated silicone oil (platinum catalyst) 1 to 10 parts

[0058] Embodiment 2:

[0059] Polyimide plain fabric with a denier of 1000D was used. The silicone rubber coating was composed of phenyl silicone rubber and iron oxide, with a viscosity of 8000CPS, an upper coating amount of 200g / ㎡, and a lower coating amount of 400g / ㎡. The tensile strength of the material before and after the heat resistance test was tested, and the results are shown in Table 1.

[0060] Components and proportions of the upper silicone rubber coating:

[0061] Hydroxyl-terminated phenyl silicone rubber (viscosity 6000CPS)……………100 parts

[0062] White carbon black 3 parts

[0063] Flake graphite………………5 parts

[0064] Talcum powder………………2 parts

[0065] Iron oxide………………1 part

[0066] Ethyl orthosilicate (organic tin catalyst) 1 to 10 parts

[0067] Components and proportions of the lower silicone rubber coating:

[0068] Hydroxyl-terminated phenyl silicone rubber (viscosity 6000CPS)……………100 parts

[0069] White carbon black…………10 parts

[0070] Kaolin 5 parts

[0071] Mica powder………………5 parts

[0072] Iron oxide………………1 part

[0073] Ethyl orthosilicate (organic tin catalyst) 1 to 10 parts

[0074] Embodiment 3:

[0075] Aramid plain fabric with a denier of 1500D is used. The silicone rubber coating is composed of phenyl silicone rubber and iron oxide, with a viscosity of 8000CPS, an upper coating amount of 200g / ㎡, and a lower coating amount of 600g / ㎡.

[0076] The tensile strength of the materials before and after the heat resistance test was tested respectively, and the results are shown in Table 1.

[0077] Components and proportions of the upper silicone rubber coating:

[0078] Vinyl phenyl silicone rubber (viscosity 8000CPS)……………100 parts

[0079] White carbon black…………10 parts

[0080] Flake graphite………………5 parts

[0081] Tetrafluoroethylene powder……………5 parts

[0082] Iron oxide………………1 part

[0083] Hydrogenated silicone oil (platinum catalyst) 1 to 10 parts

[0084] Components and proportions of the lower silicone rubber coating:

[0085] Vinyl phenyl silicone rubber (viscosity 8000CPS)……………100 parts

[0086] White carbon black 5 parts

[0087] Boron oxide 5 parts

[0088] Flake graphite………………5 parts

[0089] Iron oxide 5 parts

[0090] Mica powder………………1 part

[0091] Hydrogenated silicone oil (platinum catalyst) 1 to 10 parts

[0092] Embodiment 4:

[0093] Aramid plain fabric with a denier of 1800D is used. The silicone rubber coating is composed of phenyl silicone rubber and iron oxide, with a viscosity of 10000CPS, a coating amount of 400g / ㎡ on the upper layer, and a coating amount of 600g / ㎡ on the lower layer.

[0094] The tensile strength of the materials before and after the heat resistance test was tested respectively, and the results are shown in Table 1.

[0095] Components and proportions of the upper silicone rubber coating:

[0096] Vinyl phenyl silicone rubber (viscosity 8000CPS)……………100 parts

[0097] White carbon black…………10 parts

[0098] Tetrafluoroethylene powder……………5 parts

[0099] Iron oxide 3 parts

[0100] Flake graphite……………1 part

[0101] Hydrogenated silicone oil (platinum catalyst) 1 to 10 parts

[0102] Components and proportions of the lower silicone rubber coating:

[0103] Vinyl phenyl silicone rubber (viscosity 8000CPS)……………100 parts

[0104] White carbon black 5 parts

[0105] Boron oxide 5 parts

[0106] Iron oxide 5 parts

[0107] Mica powder………………5 parts

[0108] Kaolin………………1 part

[0109] Hydrogenated silicone oil (platinum catalyst) 1 to 10 parts

[0110] Embodiment 5:

[0111] The polyimide twill fabric with a denier of 1500D is used. The silicone rubber coating is composed of phenyl silicone rubber and iron oxide, with a viscosity of 12000CPS, a coating amount of 300g / ㎡ on the upper layer, and a coating amount of 500g / ㎡ on the lower layer.

[0112] The tensile strength of the materials before and after the heat resistance test was tested respectively, and the results are shown in Table 1.

[0113] Components and proportions of the upper silicone rubber coating:

[0114] Vinyl silicone rubber (viscosity 6000CPS)……………100 parts

[0115] White carbon black…………10 parts

[0116] Tetrafluoroethylene powder……………5 parts

[0117] Iron oxide………………4 parts

[0118] Flake graphite……………1 part

[0119] Hydrogenated silicone oil (platinum catalyst) 1 to 10 parts

[0120] Components and proportions of the lower silicone rubber coating:

[0121] Vinyl silicone rubber (viscosity 6000CPS)……………100 parts

[0122] White carbon black 8 parts

[0123] Boron oxide 5 parts

[0124] Iron oxide 5 parts

[0125] Mica powder………………1 part

[0126] Kaolin………………1 part

[0127] Hydrogenated silicone oil (platinum catalyst) 1 to 10 parts

[0128] Embodiment 6:

[0129] Polyimide square fabric with a denier of 1000D was used. The silicone rubber coating was composed of phenyl silicone rubber and iron oxide, with a viscosity of 7000CPS, an upper coating amount of 200g / ㎡, and a lower coating amount of 400g / ㎡. The tensile strength of the material before and after the heat resistance test was tested, and the results are shown in Table 1.

[0130] Components and proportions of the upper silicone rubber coating:

[0131] Hydroxyl-terminated silicone rubber (viscosity 6000CPS)……………100 parts

[0132] White carbon black 3 parts

[0133] Flake graphite………………5 parts

[0134] Talcum powder………………2 parts

[0135] Iron oxide………………1 part

[0136] Silicon dioxide………………1 part

[0137] Ethyl orthosilicate (organic tin catalyst) 1 to 10 parts

[0138] Components and proportions of the lower silicone rubber coating:

[0139] Hydroxyl-terminated silicone rubber (viscosity 6000CPS)……………100 parts

[0140] White carbon black…………10 parts

[0141] Kaolin 5 parts

[0142] Mica powder………………2 parts

[0143] Iron oxide 2 parts

[0144] Calcium silicate 1 part

[0145] Ethyl orthosilicate (organic tin catalyst) 1 to 10 parts

[0146] Embodiment 7:

[0147] Aramid twill fabric with a denier of 1200D was used. The silicone rubber coating was composed of phenyl silicone rubber and iron oxide, with a viscosity of 15000CPS, an upper coating amount of 200g / ㎡, and a lower coating amount of 400g / ㎡. The tensile strength of the material before and after the heat resistance test was tested, and the results are shown in Table 1.

[0148] Components and proportions of the upper silicone rubber coating:

[0149] Hydroxyl-terminated silicone rubber (viscosity 6000CPS)……………100 parts

[0150] White carbon black 5 parts

[0151] Flake graphite………………5 parts

[0152] Iron oxide 5 parts

[0153] Molybdenum disulfide 3 parts

[0154] Silicon dioxide………………1 part

[0155] Ethyl orthosilicate (organic tin catalyst) 1 to 10 parts

[0156] Components and proportions of the lower silicone rubber coating:

[0157] Hydroxyl-terminated silicone rubber (viscosity 6000CPS)……………100 parts

[0158] White carbon black…………10 parts

[0159] Boron oxide 5 parts

[0160] Iron oxide 5 parts

[0161] Calcium silicate 1 part

[0162] Ethyl orthosilicate (organic tin catalyst) 1 to 10 parts

[0163] Embodiment 8:

[0164] Aramid square fabric with a denier of 1000D is used. The silicone rubber coating is composed of phenyl silicone rubber and iron oxide, with a viscosity of 8000CPS, a coating amount of 300g / ㎡ on the upper layer, and a coating amount of 500g / ㎡ on the lower layer.

[0165] The tensile strength of the material was tested before and after the heat resistance test, and the results are shown in Table 1.

[0166] Components and proportions of the upper silicone rubber coating:

[0167] Vinyl silicone rubber (viscosity 6000CPS)……………100 parts

[0168] White carbon black…………10 parts

[0169] Tetrafluoroethylene powder……………5 powder

[0170] Iron oxide………………4 parts

[0171] Flake graphite……………1 part

[0172] Hydrogenated silicone oil (platinum catalyst) 1 to 10 parts

[0173] Components and proportions of the lower silicone rubber coating:

[0174] Vinyl silicone rubber (viscosity 6000CPS)……………100 parts

[0175] Iron oxide………………10 parts

[0176] White carbon black 5 parts

[0177] Boron oxide 3 parts

[0178] Mica powder……………3 parts

[0179] Kaolin………………1 part

[0180] Hydrogenated silicone oil (platinum catalyst) 1 to 10 parts

[0181] Embodiment 9:

[0182] The polyimide plain fabric with a denier of 1000D is used. The silicone rubber coating is composed of phenyl silicone rubber and iron oxide, with a viscosity of 8000CPS, a coating amount of 300g / ㎡ on the upper layer, and a coating amount of 500g / ㎡ on the lower layer.

[0183] The tensile strength of the materials before and after the heat resistance test was tested respectively, and the results are shown in Table 1.

[0184] Components and proportions of the upper silicone rubber coating:

[0185] Vinyl silicone rubber (viscosity 6000CPS)……………50 parts

[0186] Vinyl phenyl silicone rubber (viscosity 6000CPS)……………50 parts

[0187] White carbon black…………10 parts

[0188] Iron oxide………………8 parts

[0189] Flake graphite……………1 part

[0190] Silicon dioxide………………1 part

[0191] Hydrogenated silicone oil (platinum catalyst) 1 to 10 parts

[0192] Components and proportions of the lower silicone rubber coating:

[0193] Vinyl silicone rubber (viscosity 6000CPS)……………50 parts

[0194] Vinyl phenyl silicone rubber (viscosity 6000CPS)……………50 parts

[0195] Iron oxide………………10 parts

[0196] White carbon black 5 parts

[0197] Boron oxide 5 parts

[0198] Flake graphite……………1 part

[0199] Mica powder………………1 part

[0200] Hydrogenated silicone oil (platinum catalyst) 1 to 10 parts

[0201] Embodiment 10:

[0202] The polyimide twill fabric with a denier of 1200D is used. The silicone rubber coating is composed of phenyl silicone rubber and iron oxide, with a viscosity of 8000CPS, a coating amount of 300g / ㎡ on the upper layer, and a coating amount of 500g / ㎡ on the lower layer.

[0203] The tensile strength of the material was tested before and after the heat resistance test, and the results are shown in Table 1.

[0204] Components and proportions of the upper silicone rubber coating:

[0205] Hydroxyl-terminated silicone rubber (viscosity 6000CPS)……………30 parts

[0206] Hydroxyl-terminated phenyl silicone rubber (viscosity 6000CPS)……………70 parts

[0207] Iron oxide………………10 parts

[0208] Flake graphite………………5 parts

[0209] Tetrafluoroethylene powder……………3 parts

[0210] Silicon dioxide………………1 part

[0211] Ethyl orthosilicate (organic tin catalyst) 1 to 10 parts

[0212] Components and proportions of the lower silicone rubber coating:

[0213] Hydroxyl-terminated silicone rubber (viscosity 6000CPS)……………30 parts

[0214] Hydroxyl-terminated phenyl silicone rubber (viscosity 6000CPS)……………70 parts

[0215] Iron oxide………………10 parts

[0216] White carbon black 5 parts

[0217] Lanthanum oxide 5 parts

[0218] Calcium silicate 1 part

[0219] Ethyl orthosilicate (organic tin catalyst) 1 to 10 parts

[0220] Embodiment 11:

[0221] The polyimide plain fabric with a denier of 1200D is used. The silicone rubber coating is composed of phenyl silicone rubber and iron oxide, with a viscosity of 8000CPS, a coating amount of 300g / ㎡ on the upper layer, and a coating amount of 500g / ㎡ on the lower layer.

[0222] The tensile strength of the materials before and after the heat resistance test was tested respectively, and the results are shown in Table 1.

[0223] Components and proportions of the upper silicone rubber coating:

[0224] Hydroxyl-terminated silicone rubber (viscosity 6000CPS)……………50 parts

[0225] Hydroxyl-terminated phenyl silicone rubber (viscosity 6000CPS)……………50 parts

[0226] Iron oxide………………10 parts

[0227] Flake graphite………………5 parts

[0228] Tetrafluoroethylene powder……………3 parts

[0229] Silicon dioxide………………1 part

[0230] Ethyl orthosilicate (organic tin catalyst) 1 to 10 parts

[0231] Components and proportions of the lower silicone rubber coating:

[0232] Hydroxyl-terminated silicone rubber (viscosity 6000CPS)……………50 parts

[0233] Hydroxyl-terminated phenyl silicone rubber (viscosity 6000CPS)……………50 parts

[0234] Iron oxide………………10 parts

[0235] White carbon black 5 parts

[0236] Lanthanum oxide 5 parts

[0237] Calcium silicate 1 part

[0238] Ethyl orthosilicate (organic tin catalyst) 1 to 10 parts

[0239] Embodiment 12:

[0240] The polyimide plain fabric with a denier of 1200D is used. The silicone rubber coating is composed of phenyl silicone rubber and iron oxide, with a viscosity of 8000CPS, a coating amount of 300g / ㎡ on the upper layer, and a coating amount of 500g / ㎡ on the lower layer.

[0241] The tensile strength of the materials before and after the heat resistance test was tested respectively, and the results are shown in Table 1.

[0242] Components and proportions of the upper silicone rubber coating:

[0243] Hydroxyl-terminated silicone rubber (viscosity 6000CPS)……………40 parts

[0244] Hydroxyl-terminated phenyl silicone rubber (viscosity 6000CPS)……………60 parts

[0245] Iron oxide………………10 parts

[0246] Flake graphite………………5 parts

[0247] Tetrafluoroethylene powder……………3 parts

[0248] Silicon dioxide………………1 part

[0249] Ethyl orthosilicate (organic tin catalyst) 1 to 10 parts

[0250] Components and proportions of the lower silicone rubber coating:

[0251] Hydroxyl-terminated silicone rubber (viscosity 6000CPS)……………40 parts

[0252] Hydroxyl-terminated phenyl silicone rubber (viscosity 6000CPS)……………60 parts

[0253] Iron oxide………………10 parts

[0254] White carbon black 5 parts

[0255] Lanthanum oxide 5 parts

[0256] Calcium silicate 1 part

[0257] Ethyl orthosilicate (organic tin catalyst) 1 to 10 parts

[0258] The tensile strength of the material was tested before and after the heat resistance test, and the results are shown in Table 1.

[0259] Table 1 Test results of high temperature resistant and high strength underwater recovery airbag materials

[0260] Tensile strength before heat resistance test (N) Tensile strength after heat resistance test (N) Strength reduction rate Example 1 2630 2472.9 6% Example 2 6340 5896.5 7% Example 3 7820 7429.3 5% Example 4 9384 8891.4 5% Example 5 9110 8618.3 5% Example 6 6450 6062.1 6% Example 7 6256 5882.9 6% Example 8 5216 4858.2 7% Example 9 6420 6125.2 5% Example 10 7532 7116.5 6% Embodiment 11 7422 7000.2 6% Example 12 7768 7222.1 7%

[0261] It can be seen from Table 1 that the high-temperature resistant and high-strength underwater recovery airbag material using the technical solution of the present invention has high strength and excellent heat resistance.

Claims

1. A high-temperature resistant and high-strength underwater recovery airbag material for underwater equipment flotation device, comprising a high-strength fiber base cloth, an upper silicone rubber coating and a lower silicone rubber coating, characterized in that: The high-strength fiber base fabric is composed of aramid fiber filaments or polyimide fiber filaments; the upper silicone rubber coating and the lower silicone rubber coating are coated on the inner and outer sides of the high-strength fiber base fabric, respectively, corresponding to the inner and outer sides of the airbag after the airbag is formed; The components and proportions of the upper silicone rubber coating are: Silicone elastomer………………100 parts Functional filler…………10~20 parts Vulcanizing agent…………1~10 parts The components and proportions of the lower silicone rubber coating are: Silicone elastomer 100 parts Inorganic filler…………20~30 parts Vulcanizing agent…………1~10 parts Wherein, the organic silicon elastomer is one or a mixture of vinyl silicone rubber, vinyl phenyl silicone rubber, hydroxyl-terminated silicone rubber and hydroxyl-terminated phenyl silicone rubber.

2. The high temperature resistant and high strength underwater recovery airbag material according to claim 1, characterized in that: The high-strength fiber base cloth adopts a woven structure.

3. The high temperature resistant and high strength underwater recovery airbag material according to claim 2 is characterized in that: The high-strength fiber base cloth weaving structure is a plain weave, a twill weave or a square basket structure.

4. The high temperature resistant and high strength underwater recovery airbag material according to claim 2, characterized in that: The fiber filament denier is 300-2000D.

5. The high temperature resistant and high strength underwater recovery airbag material according to claim 3, characterized in that: The surface density of the high-strength fiber-based fabric is 200-400g / ㎡.

6. The high temperature resistant and high strength underwater recovery airbag material according to claim 1, characterized in that: The surface density of the lower silicone rubber coating is 400-700g / ㎡.

7. The high temperature resistant and high strength underwater recovery airbag material according to claim 1, characterized in that: The surface density of the upper silicone rubber coating is 200-420 g / ㎡.

8. The high temperature resistant and high strength underwater recovery airbag material according to claim 1, characterized in that: The functional filler is one or a mixture of iron oxide, silicon dioxide, flaky graphite, talcum powder, molybdenum disulfide or tetrafluoroethylene powder.

9. The high temperature resistant and high strength underwater recovery airbag material according to claim 1, characterized in that: The inorganic filler is one or a mixture of iron oxide, silicon dioxide, carbon black, flaky graphite, lanthanum oxide, boron oxide, calcium silicate, mica powder or kaolin.

10. The high temperature resistant and high strength underwater recovery airbag material according to claim 1, characterized in that: The viscosity of the upper silicone rubber coating and the lower silicone rubber coating is 4000-20000 CPS.